Upregulation of the Nifhdken Operon in Leptospirillum Species Subjected to Soluble Nitrogen Starvation - Corbett, Melissa; Mutch, Lesley; Watkin, Elizabeth (Nature Publishing Group, 2008)
Background: Members of the genus Leptospirillum routinely dominate bioleaching systems. Understanding their metabolic complexity is necessary for the improvement of bioleaching technologies. Nitrogen is an essential element required for the cellular growth of all microorganisms. In this study Leptospirillum species were assessed for their nitrogen fixation capabilities under aerobic and anaerobic conditions, in the absence of soluble ammonia.